2018
DOI: 10.1111/hepr.13246
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy and safety of sofosbuvir + ribavirin for hepatitis C genotype 2: A nationwide multicenter study by the Japanese Red Cross Liver Study Group

Abstract: Treatment with SOF + RBV was highly effective and safe in Japanese patients with HCV genotype 2 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 39 publications
3
38
1
Order By: Relevance
“…This nationwide observational multicenter study was undertaken by the Japanese Red Cross Liver Study Group, including 24 centers of Japanese Red Cross Hospitals. Previously, we reported that the overall SVR rate for GT2 patients treated with SOF + RBV was 96.8% in a multicenter cohort . Until March 2019, we accumulated 28 patients who failed prior SOF + RBV regimens and were retreated with GLE/PIB for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This nationwide observational multicenter study was undertaken by the Japanese Red Cross Liver Study Group, including 24 centers of Japanese Red Cross Hospitals. Previously, we reported that the overall SVR rate for GT2 patients treated with SOF + RBV was 96.8% in a multicenter cohort . Until March 2019, we accumulated 28 patients who failed prior SOF + RBV regimens and were retreated with GLE/PIB for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Direct‐acting antiviral therapies have consistently shown high sustained virologic response (SVR) rates, good tolerability, and efficacy with shorter treatment durations. For HCV genotype 2 (GT2), the sofosbuvir (SOF) plus RBV regimen attained a high SVR rate in the real‐world setting . Conversely, rescue therapy for GT2 patients who failed prior SOF + RBV regimens remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) is the leading cause of death in patients with chronic hepatitis C. In recent years, direct‐acting antiviral (DAA) treatment has enabled many patients to achieve sustained virological responses (SVR) . Thus, it is expected that the development of HCC will be suppressed .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of new direct‐acting antivirals (DAAs) have been developed that selectively target HCV proteins. Sofosbuvir (SOF) is an oral nucleotide analog inhibitor of the HCV non‐structural protein 5B polymerase that is effective for treating HCV GT2 when given in combination with RBV . However, the most commonly reported adverse event was RBV‐induced hemolytic anemia, which resulted in dose reduction of RBV …”
Section: Introductionmentioning
confidence: 99%